Bio-VLab: Virtual Laboratory Based on Android Educational Game - Putri Sabilla Aulia Najiyah; Reza Fauzi Dwisandi; Muhammad Nizar Maulana; Diana Hernawati (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
Virtual reality has a lot of potentials to be applied in the field of education and learning, known as virtual learning. For some learning activities there is quite a lot of interest in research about virtual learning. However, at present there is little virtual learning in the packaging of a virtual laboratory based on an Android educational game that presents a series of practical activities as a form of verification or confirmation of concepts learned by students. For this reason, this research aims to develop Bio-VLab, a game-based android mobile application, by adopting some of the ADDIE development procedures covering the analysis and design stages. Technical analysis was carried out descriptively qualitatively based on prototypes generated from the design of the development including initial appearance, class choices, list of materials, learning objectives, display of teaching aids, and practical content.